Unraveling the ECM-Immune Cell Crosstalk in Skin Diseases - Bhattacharjee, Oindrila; Ayyangar, Uttkarsh; Kurbet, Ambika S.; Ashok, Driti; Raghavan, Srikala (Frontiers in Cell and Developmental Biology, 2019)
The extracellular matrix (ECM) is a complex network of proteins and proteoglycans secreted by keratinocytes, fibroblasts and immune cells. The function of the skin ECM has expanded from being a scaffold that provides structural integrity, to a more dynamic entity that is constantly remodeled to maintain tissue homeostasis. ECMs function as ligands for cell surface receptors such as integrins, dystroglycans and toll-like receptors (TLRs) and regulate cellular signaling and immune cell dynamics. The ECM also acts as a sink for growth factors and cytokines, providing critical cues during epithelial morphogenesis. Dysregulation in the organization and deposition of ECMs lead to a plethora of pathophysiological conditions that are exacerbated by aberrant ECM-immune cell interactions. In this review, we focus on the interplay between ECM and immune cells in the context of skin diseases and also discuss state of the art therapies that target the key molecular players involved.